Pengaruh Beban Kerja terhadap Kinerja Karyawan Perumda Air Minum Tirta Ratu Samban Bengkulu Utara Dimediasi Perilaku Cyberloafing - Ovika, Maulida Nabila; Praningrum, Praningrum (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to investigate the effect of workload on employee performance at Perumda Air Minum Tirta Ratu Samban, North Bengkulu by considering cyberloafing behavior as a mediating variable. In this research, the author will use a quantitative approach to collect and analyze data. The research method used is a quantitative method. Total population 100 employees and the number of samples used in this research was 65 respondents. Data was collected by distributing questionnaires via a Google Form link. The multiple linear regression method is used to analyze the influence of the independent variable on the dependent variable. and the samples used in the research used non-probability Keywords: Workload,Performance,Cyberloafing